Kompozicija tela i vrhunska snaga kod madarskih sportista medunarodnog ranga - Meszaros, J.; Soliman, Y.; Othman, M.; Mohacsi, J. (Facta Universitatis: Series Physical Education and Sport, 1998)
As an independent aspects, body size, physique, body composition and physiological performance of elite athletes have aroused the interest of exercise scientists, but studies that combine these aspects in elite athletes are scarcely available. The aim of the present study was to describe the selected anthropometric and exercise physiological characteristics of some Hungarian top athletes. The investigated subjects were qualified Hungarian water polo players (n = 25), paddlers (n = 24) and modern pentathlonists (n = 20), all of whom had been medalists at several continental and intercontinental competitions. The athletes' body composition was estimated by the Drinkwater-Ross (1980) body mass fractionation technique. Peak physiological performance was estimated by graded exhausting spiroergometric treadmill exercise. Intergroup differences in mean height, body mass and body composition characteristics were significant at the 5% level of random error. By the results of spiroergometry, all the three groups compared could be qualified as physically excellently trained. The greatest oxygen uptake relative to body mass was found in the modern pentathlonists (73.22 mL x kg-1 x min-1) and the lowest one (59.79) in the water polo players. The authors do not disregard the favourable effects of regular and adequate trainings in the development of the studied characteristics, but in their opinion the process of proper selection has been the most important factor that explains the observed significant intergroup differences.